(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Life cycle assessment (LCA) in the building sector has become a widely used method for quantifying environmental impacts of a building over its entire life cycle. Currently, however, no standardized procedure exists for considering refurbishment measures. In addition, the LCA, according to the European standard EN 15978, is limited to building level only. This paper shows how a methodological LCA framework of refurbishment methods can be applied at three levels: single building, neighbourhood, and municipality. Initially, the proposed methodological approaches are introduced while the framework rules are defined for each of the three levels. The system boundaries of the LCA differ regarding the assessment levels within the given methodology and are adapted accordingly. In addition, the three levels of assessment are defined by the accuracy of measurement results, and data requirements, as well as by the specific value of the calculations and the ownership of the building stock. The assessment levels provide a specific quality and quantity of environmental indicator results. Thus, the complex interrelationships of the assessment levels are shown. The developed framework for the environmental assessment of refurbishment measures provides comparability at the building level. At the neighbourhood level, emissions from refurbishment measures are compared with the reductions of emissions through heating energy demand. Ultimately, the potential of refurbishment measures at the municipal level can be identified on a large scale and used as a decision-making tool.